The Influence of Non-Performing Financing and Financing to Deposit Ratio on Profitability with Capital Adequacy Ratio as a Mediation Variable on Islamic Commercial Banks in Indonesia, 2020-2022 - Danik Setiarini; Fetria Eka Yudiana (Alkasb: Journal of Islamic Economics, 2023)
The purpose of this study is to analyze the influence of Non-Performing Finance and Financing to Deposit Ratio on Profitability with Capital Adequacy ratio as a moderating variable at Islamic Commercial Banks in Indonesia for the 2020-2022 period. This research is a quantitative type of research that uses secondary data in the form of panel data. The sample used in this research is four banks registered with the Financial Services Authority and which have published their annual reports for the 2020-2022 period. The results of the tests conducted NPF has a significant effect on ROA in a positive direction, FDR has a positive but not significant effect on ROA, CAR has a significant positive effect on ROA, NPF has a significant effect on CAR with a negative correlation, FDR has a significant positive effect to CAR, CAR is not able to mediate the relationship between NPF and ROA, and CAR can be a variable mediating the relationship between FDR and ROA.